Kinetics of the Reaction of Methyl Radical with Methanol - Huu Tho, Nguyen; Sang, Nguyen Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 1DO - 10.25073/2588-1140/vnunst.4725, 2018)
This work studied theoretically in details the mechanism, kinetics and thermochemistry of reactions of methyl radical with methanol. The theoretical study was carried out by ab initio molecular orbital theory based on CCSD(T)/B3LYP/6-311++G(3df,2p) methods in conjunction variational transition state theory (VTST). Calculated results showed that, in the temperature range from 300K to 2000K, and the pressure at 760 Torr, temperature dependent rate constants of the reactions were: CH 3 + CH 3 OH ® CH 4 + CH 2 OH    k(T) = 2.146´10 -27 .T 4.64 .exp(-33.47[kJ/mol/RT), CH 3 + CH 3 OH ® CH 4 + CH 3 O       k(T) = 2.583´10 -27 .T 4.52 .exp(-29.56[kJ/mol/RT), CH 3 + CH 3 OH ® H + CH 3 OCH 3    k(T) = 1.025´10 -23 .T 3.16 .exp(-186.84[kJ/mol/RT) When the reaction temperature is above 730 K, the abstraction process of H in –CH 3 group of methanol will occur faster. The abstraction process of H in –OH group dominates when the reaction temperature is below 730 K. Keywords Kinetic, methyl, methanol, ab initio References 1. Slagle, I.R., D. Sarzynski, and D. Gutman, Kinetics of the reaction between methyl radicals and oxygen atoms between 294 and 900 K. The Journal of Physical Chemistry, 1987. 91(16): p. 4375-4379. 2. Rutz L., B.H., Bozzelli J. W., Methyl Radical and Shift Reactions with Aliphatic and Aromatic Hydrocarbons: Thermochemical Properties, Reaction Paths and Kinetic Parameters. American Chemical Society, Division Fuel Chemistry, 2004. 49(1): p. 451-452. 3. Johnson, D.G., M.A. Blitz, and P.W. Seakins, The reaction of methylidene (CH) with methanol isotopomers. Physical Chemistry Chemical Physics, 2000. 2(11): p. 2549-2553. 4. Cribb, P.H., J.E. Dove, and S. Yamazaki, A kinetic study of the pyrolysis of methanol using shock tube and computer simulation techniques. Combustion and Flame, 1992. 88(2): p. 169-185. 5. Dombrowsky, C., et al., An Investigation of the Methanol Decomposition Behind Incident Shock Waves. Berichte der Bunsengesellschaft für physikalische Chemie, 1991. 95(12): p. 1685-1687. 6. Krasnoperov, L.N. and J.V. Michael, High-Temperature Shock Tube Studies Using Multipass Absorption:  Rate Constant Results for OH + CH3, OH + CH2, and the Dissociation of CH3OH. The Journal of Physical Chemistry A, 2004. 108(40): p. 8317-8323. 7. Shannon, T.W. and A.G. Harrison, The reaction of methyl radicals with methyl alcohol. Canadian Journal of Chemistry, 1963. 41(10): p. 2455-2461. 8. Jodkowski, J.T., et al., Theoretical Study of the Kinetics of the Hydrogen Abstraction from Methanol. 3. Reaction of Methanol with Hydrogen Atom, Methyl, and Hydroxyl Radicals. The Journal of Physical Chemistry A, 1999. 103(19): p. 3750-3765. 9. Alecu, I.M. and D.G. Truhlar, Computational Study of the Reactions of Methanol with the Hydroperoxyl and Methyl Radicals. 2. Accurate Thermal Rate Constants. The Journal of Physical Chemistry A, 2011. 115(51): p. 14599-14611. 10. Peukert, S.L. and J.V. Michael, High-Temperature Shock Tube and Modeling Studies on the Reactions of Methanol with D-Atoms and CH3-Radicals. The Journal of Physical Chemistry A, 2013. 117(40): p. 10186-10195. 11. Anastasi, C. and D.U. Hancock, Reaction of CH3 radicals with methanol in the range 525 <T/K < 603. Journal of the Chemical Society, Faraday Transactions, 1990. 86(14): p. 2553-2555. 12. Dombrowsky, C. and H.G. Wagner, An investigation of the reaction between CH3 radicals and methanol at high temperatures. Berichte der Bunsengesellschaft für physikalische Chemie, 1989. 93(5): p. 633-637. 13. Tsang, W., Chemical Kinetic Data Base for Combustion Chemistry. Part 2. Methanol. Journal of Physical and Chemical Reference Data, 1987. 16(3): p. 471-508. 14. Becke, A.D., Density‐functional thermochemistry. II. The effect of the Perdew–Wang generalized‐gradient correlation correction. The Journal of Chemical Physics, 1992. 97(12): p. 9173-9177. 15. Becke, A.D., Density‐functional thermochemistry. I. The effect of the exchange‐only gradient correction. The Journal of Chemical Physics, 1992. 96(3): p. 2155-2160. 16. Becke, A.D., Density‐functional thermochemistry. III. The role of exact exchange. The Journal of Chemical Physics, 1993. 98(7): p. 5648-5652. 17. Yang, W., R.G. Parr, and C. Lee, Various functionals for the kinetic energy density of an atom or molecule. Physical Review A, 1986. 34(6): p. 4586-4590. 18. Hehre W. , R.L., Schleyer P. V. R. , and Pople J. A. and 30, Ab Initio Molecular Orbital Theory. 1986, New York: Wiley. 19. Andersson, M.P. and P. Uvdal, New Scale Factors for Harmonic Vibrational Frequencies Using the B3LYP Density Functional Method with the Triple-ζ Basis Set 6-311+G(d,p). The Journal of Physical Chemistry A, 2005. 109(12): p. 2937-2941. 20. Raghavachari, K., et al., A fifth-order perturbation comparison of electron correlation theories. Chemical Physics Letters, 1989. 157(6): p. 479-483. 21. M.J. Frisch, G.W.T., H.B. Schlegel, et al., GAUSSIAN 09, Revision C.01, Gaussian Inc., Wallingford CT, 2010. 22. Robson Wright, M., Theories of Chemical Reactions, in An Introduction to Chemical Kinetics. 2005, John Wiley & Sons, Ltd. p. 99-164. 23. Goos, E.B., A.; Ruscic, B., Extended Third Millennium Ideal Gas and Condensed Phase Thermochemical Database for Combustion with Updates from Active Thermochemical Tables. http://garfield.chem.elte.hu/Burcat/burcat.html, October, 2017.